2019
DOI: 10.32964/tj18.8.499
|View full text |Cite
|
Sign up to set email alerts
|

Progress in foam forming technology

Abstract: This paper summarizes recent developments in foam forming that were mainly carried out in pilot scale. In addition to improving the efficiency of existing processes and allowing better uniformity in material, a wide variety of raw materials can be utilized in foam forming. The focus of this paper is thin webs—papers, boards and foam-laid nonwovens, along with the pilot scale results obtained at VTT in Finland. For paper and board grades, the most direct advantage of foam forming is the potential to produce ver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 31 publications
0
12
0
Order By: Relevance
“…[76] After a few decades in late 2000s, interest in foam-forming technology was raised again, and several pilot-scale studies have been published during the last 10 years. [4][5][6]18,45,[106][107][108]…”
Section: Manufacturing Process Operationsmentioning
confidence: 99%
See 3 more Smart Citations
“…[76] After a few decades in late 2000s, interest in foam-forming technology was raised again, and several pilot-scale studies have been published during the last 10 years. [4][5][6]18,45,[106][107][108]…”
Section: Manufacturing Process Operationsmentioning
confidence: 99%
“…They reported a 10% bulk increase in middleply at the equal internal strength level. Kiiskinen et al [6] reported pilot-scale results for a single-ply board from CTMP pulp. In their study, the increase in bulk of the foam-formed board was 18-20% higher compared to water-laid reverence at a given press solids content level (Figure 33).…”
Section: Packaging Boardsmentioning
confidence: 99%
See 2 more Smart Citations
“…How valuable would it be if an existing production line could be used to produce higher value or even entirely new products? To respond to this challenge, foam forming technology has attracted much attention during the past few years (Lehmonen et al 2013;Kinnunen-Raudaskoski 2017;Kiiskinen et al 2019;Lehmonen et al 2019). Foam forming utilizes small air bubbles (average bubble radius < 100 µm) containing aqueous foam instead of pure water as a process fluid and flowing medium.…”
Section: Introductionmentioning
confidence: 99%